2014
DOI: 10.1111/ases.12107
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy assisted middle‐segment–preserving pancreatectomy for multiple pancreatic neuroendocrine tumors: Report of a case

Abstract: For multiple low-grade malignant tumors located in the pancreatic head and tail, middle-segment-preserving pancreatectomy (MSPP) is sometimes indicated. However, MSPP has rarely been performed laparoscopically. Here we report the first case of laparoscopic MSPP for multiple pancreatic neuroendocrine tumors diagnosed preoperatively under an endoscopic ultrasound-guided fine-needle aspiration biopsy. A 70-year-old man had multiple small tumors located in the pancreatic head, body and tail. Endoscopic ultrasound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Indications for MPP are pancreatic body-sparing multifocal disease, including PDAC, [9,20] IPMNs, [24,32] neuroendocrine tumors (PNETs), [21,31] and metastatic tumors of the pancreas with a low-grade malignant nature. [23,29,30] In our current series, the major indications were metastatic tumors of the pancreas, including renal cell carcinoma (RCC), DFSP, and pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for MPP are pancreatic body-sparing multifocal disease, including PDAC, [9,20] IPMNs, [24,32] neuroendocrine tumors (PNETs), [21,31] and metastatic tumors of the pancreas with a low-grade malignant nature. [23,29,30] In our current series, the major indications were metastatic tumors of the pancreas, including renal cell carcinoma (RCC), DFSP, and pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have recommended MSPP for patients with multicentric noninvasive lesions, such as IPMNs, and pancreatic metastases, because lymphadenectomy was not necessary [ 6 , 8 – 10 ]. Recently, as a minimally invasive surgery, laparoscopy-assisted MSPP was also reported [ 11 ]. Cheng et al [ 6 ] reviewed 22 patients who underwent MSPP and showed that the overall morbidity was 40.9% (9/22), especially pancreatic fistula was 22.7% (5/22) with no mortality.…”
Section: Case Presentationmentioning
confidence: 99%